Report on homes of the poor - Falkiner, F. R. (Statistical and Social Inquiry Society of Ireland, 1882)
The state of the dwellings of the working and poorer population has been now so fully recognized as one of the most potent causes of all that is deplorable in the sanitary and social conditions of this city, that we do not think it necessary here to enter upon the proofs. These are to be found at large in the Report, dated June, 1880, of the Royal Commission on the sewerage and drainage of Dublin, which sat in the autumn of 1879, and the voluminous evidence thereto appended.
Papers read by members of the society at the social science congress, Dublin, October 1881
Keywords: Poverty; Housing conditions; Public health; 314.15